2017
DOI: 10.1038/ng.3922
|View full text |Cite
|
Sign up to set email alerts
|

PRDM15 safeguards naive pluripotency by transcriptionally regulating WNT and MAPK–ERK signaling

Abstract: The transcriptional network acting downstream of LIF, WNT and MAPK-ERK to stabilize mouse embryonic stem cells (ESCs) in their naive state has been extensively characterized. However, the upstream factors regulating these three signaling pathways remain largely uncharted. PR-domain-containing proteins (PRDMs) are zinc-finger sequence-specific chromatin factors that have essential roles in embryonic development and cell fate decisions. Here we characterize the transcriptional regulator PRDM15, which acts indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 46 publications
3
71
0
Order By: Relevance
“…Instead, the expression of IL6R and the co-receptor GP130 and IL6ST was high, suggesting that IL6 but not LIF signaling plays an important role in naïve pluripotency in pig. The pattern is consistent with the previous observations that forced activation of the pathway inhibits the development of mouse embryo to the blastocyst stage 26 and inhibition of the pathway has no obvious effect on the formation of the ICM in pig. 38 In our study, MAPK pathway was found enrichment in ICM of pig, indicating the pathway is essential for advanced progression of porcine ICM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, the expression of IL6R and the co-receptor GP130 and IL6ST was high, suggesting that IL6 but not LIF signaling plays an important role in naïve pluripotency in pig. The pattern is consistent with the previous observations that forced activation of the pathway inhibits the development of mouse embryo to the blastocyst stage 26 and inhibition of the pathway has no obvious effect on the formation of the ICM in pig. 38 In our study, MAPK pathway was found enrichment in ICM of pig, indicating the pathway is essential for advanced progression of porcine ICM.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, GP130 and IL6R were significantly high in ICM. In mouse, the MAPK signaling pathway is important for formation of hypoblast 17,26 and derivation of epiblast stem cells (EpiSCs). The IF analysis of p-STAT3 reinforced the notion that the JAK-STAT signaling pathway was activated in the 2-cell embryo (n = 5) and ICM of EB (n = 3; Figure 5B).…”
Section: Enrichment Of Signaling Pathways In Porcine Pluripotent Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MAPK signaling plays an important role in CSCs self-renewal and tumorigenicity [15][16][17]. However, how MAPK signaling sustains gastric CSCs self-renewal and tumorigenicity remains largely unknown.…”
Section: Mapk Signaling Regulated the Prr11 Protein Stability Of Gastmentioning
confidence: 99%
“…The PR domain proteins, many of which have histone methyltransferase activity and others that recruit methyltransferases to DNA, play roles as molecular switches in many developmental processes (Fog et al 2012;Hohenauer and Moore 2012). Little is known about PRDM15, but it functions in pluripotency (Mzoughi et al 2017) and maps to the Down syndrome trisomy region of mouse Chromosome 16 and human Chromosome 21. ZZZ3 is a part of the Ada-Two-A-containing (ATAC) histone acetyltransferase complex, which widely regulates gene expression (Mi et al 2018).…”
Section: Candidate Genes Fall Into Similar Functional Pathwaysmentioning
confidence: 99%